So I looked it up on another math helper app called ( Socratic )and this is what popped up on my screen Simplifying
16 = 17 + -1t
Solving
16 = 17 + -1t
Solving for variable 't'.
Move all terms containing t to the left, all other terms to the right.
Add 't' to each side of the equation.
16 + t = 17 + -1t + t
Combine like terms: -1t + t = 0
16 + t = 17 + 0
16 + t = 17
Add '-16' to each side of the equation.
16 + -16 + t = 17 + -16
Combine like terms: 16 + -16 = 0
0 + t = 17 + -16
t = 17 + -16
Combine like terms: 17 + -16 = 1
t = 1
Simplifying
t = 1
So I’m pretty sure that’s the answer:) if not I’m truly sorry.